Successful Human Spermatogonial Stem Cells Homing in Recipient Mouse Testis after In Vitro Transplantation and Organ Culture - Mohaqiq, Mahdi (Cell J, 2019)
OBJECTIVE: In vitro transplantation (IVT) of spermatogonial stem cells (SSCs) is one of the most recent methods in transplantation in recent decades. In this study, IVT and SSCs homing on seminiferous tubules of host testis in organ culture have been studied. MATERIALS AND METHODS: In this experimental study, human SSCs were isolated and their identities were confirmed by tracking their promyelocytic leukemia zinc finger (PLZF) protein. These cells were transplanted to adult azoospermia mouse testes using two methods, namely, IVT and in vivo transplantation as transplantation groups, and testes without transplantation of cells were assigned in the control group. Then histomorphometric, immunohistochemical and molecular studies were done after 2 weeks. RESULTS: After two weeks, histomorphometric studies revealed that the number of subsided spermatogonial cells (SCs) and the percentage of tubules with subsided SCs in IVT and in vivo groups were significantly more than those in the control group (P<0.05). Immunohistochemical studies in the transplantation groups confirmed that the PLZF protein was expressed in the cells subsided on the seminiferous tubule. Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) demonstrated that the PLZF gene expression was only positive in the transplantation groups, but it was not significantly different between the IVT group and the in vivo group (P>0.05). CONCLUSION: Testicular tissue culture conditions after SSC transplantation can help these cells subside on the seminiferous tubule basement membrane.